2020
DOI: 10.1021/acs.est.0c02871
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Boscalid Induces Reproductive Toxicity of Zebrafish by Gender-Specific Alterations in Steroidogenesis

Abstract: Boscalid is a succinate dehydrogenase inhibitor fungicide and is frequently detected in surface water. Due to the frequent detection of boscalid, we evaluated its impact on the reproduction of adult zebrafish following a 21 d exposure to 0, 0.01, 0.1, and 1.0 mg/L. Following exposure to boscalid, the fertility of female zebrafish and fertilization rate of spawning eggs were reduced in a concentration-dependent manner up to a respective 87% and 20% in the highest concentration. A significant 16% reduction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 87 publications
2
24
0
Order By: Relevance
“…In Qian et al's study, the same phenomenon was observed in zebra sh after 21 d of exposure to boscalid (0.1 and 1.0 mg/L) (Qian et al, 2020). Not surprisingly, our results also showed that the percentage of LV, SD and SZ were signi cantly decreased in 1.0 or 10 µg/L DCZ treatment groups (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In Qian et al's study, the same phenomenon was observed in zebra sh after 21 d of exposure to boscalid (0.1 and 1.0 mg/L) (Qian et al, 2020). Not surprisingly, our results also showed that the percentage of LV, SD and SZ were signi cantly decreased in 1.0 or 10 µg/L DCZ treatment groups (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…After 120 days of DCZ exposure, six serum samples (three female serum samples and three male serum samples) were selected from each treatment group to determine the content of 17β-estradiol (E2), testosterone (T), and vitellogenin (VTG). The levels of E2, T, and VTG are detected by using enzyme-linked immunosorbent assay (ELISA) kits (MSKBIO, Wuhan, China) as previously described (Qian et al, 2020).…”
Section: Sex Steroid Hormones and Vtg Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar change was observed after 21 days of exposure to zebrafish with 1mg/L boscalid. The female fish’s fertility decreased, and the oocyte stage distribution in the ovary was abnormal, but the GSI value did not change (Qian et al, 2020). At the same time, CyB exposure also significantly affected the reproductive system of male zebrafish.…”
Section: Discussionmentioning
confidence: 99%